ΜSR investigation of a new diluted magnetic semiconductor Li(Zn, Mn, Cu)As with Mn and Cu codoping at the same Zn sites. (12th July 2016) - Guo, S L; Zhao, Y; Man, H Y; Ding, C; Gong, X; Zhi, G X; Fu, L C; Gu, Y L; Frandsen, B A; Liu, L; Cheung, S C; Munsie, T J; et al.
Abstract: We report the successful synthesis and characterization of a new type I–II–V bulk form diluted magnetic semiconductor (DMS) Li(Zn, Mn, Cu)As, in which charge and spin doping are decoupled via (Cu, Zn) and (Mn, Zn) substitution at the same Zn sites. Ferromagnetic transition temperature up to  ∼33 K has been observed with a coercive field  ∼40 Oe for the 12.5% doping level. μ SR measurements confirmed that the magnetic volume fraction reaches nearly 100% at 2 K, and the mechanism responsible for the ferromagnetic interaction in this system is the same as other bulk form DMSs.